27.26 Product Class 26: Thioaldehyde and Thioketone S-Sulfides (Thiosulfines) - Mlostoń,G.; Heimgartner,H. (Knowledge Updates 2014/2, 2014)
This chapter is an overview of methods for the in situ generation and application of highly reactive thiocarbonyl S-sulfides. Typically, thiocarbonyl S-sulfides react as sulfur-rich 1,3-dipoles and trap both electron-deficient C,C-dipolarophiles and thiocarbonyl substrates, yielding the corresponding five-membered cycloadducts. In some instances, intermediate thiocarbonyl S-sulfides and/or their cyclic isomers (i.e., dithiiranes) act as sulfur-transfer agents leading to sulfur-rich heterocycles such as pentathiepanes and hexathiepanes.
Keywords: Referencework; Science of Synthesis; dipolar cycloaddition; dithiolanes; five-membered rings; multicomponent reactions; sulfur heterocycles; thiones